Evaluation of Satisfaction and Axial Rigidity with Titan XL Cylinders. (11th September 2012) - Henry, Gerard D.; Jennermann, Caroline; Eid, J. Francois
Abstract : The inflatable penile prosthesis (IPP) has high patient satisfaction rates and good mechanical reliability rates in multiple studies. The number one patient compliant at six months is penile length. Recently, new technique for aggressive sizing of the cylinders has been published on in the literature. One IPP company has produced a new product that has longer length cylinders (XL) than those available. However, traditionally long cylinders were felt to lack axial rigidity. Therefore, a prospective, multicenter, central IRB-approved, monitored study was performed on the new product to address these concerns. At 2 centers, a total of 17 patients underwent surgical implantation of these new XL cylinders. These patients were questioned for patient satisfaction and tested for axial rigidity using a Fastsize Erectile Quality Monitor. The results showed excellent patient satisfaction rates and great axial rigidity with the Fastsize Erectile Quality Monitor. The XL cylinders appear to give the IPP surgeon the ability to use longer cylinders with good patient satisfaction and great axial rigidity.